(untitled) - Richey, C. B. (New York, 1961)
This handbook provides a comprehensive coverage of modern engineering practices relating to agricultural problems. The book contains 57 chapters divided into four sections: Crop-Production Equipment; Soil and Water Conservation; Farmstead Structures and Equipment; and Basic Agricultural Data.
Keywords: Agricultural engineering